Supporting Teachers’ Competence in Designing Learning Activities to Facilitate Students’ Engagement in Online Environment - Finita Dewi; Gumawang Jati; Tia Citra Bayuni (SEAMEO SEAMOLEC, 2023)
The new normal in education requires teachers, parents, and students to carry out online learning by utilizing various media and learning models different from before. To ensure that students continue to receive good learning services, teachers need to be equipped with technological and pedagogical knowledge to support the implementation of online learning activities during the pandemic situation. This study aims to develop online training that can equip teachers to become designers of collaborative and engaging learning activities with the help of digital technology. The method used in this study is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects are teachers who have experienced and implemented distance learning education during the pandemic. Data collection techniques were obtained from the results of tests and questionnaires. The data analysis technique used is descriptive statistics and inferential statistics. The product produced in this development is an online training that can develop the teachers’ ability to design lessons that can facilitate students’ engagement. The study results indicate that the product developed has a good validity value to be used at the implementation stage. The implementation results show that the online training has supported teachers in designing collaborative, innovative, and applicable learning activities. In addition, users show positive responses towards the activities in the online training. In conclusion, this online training can be considered valid and feasible and recommended to be disseminated for a wider audience.